Identify the inverse g(x) of the given relation f(x).
f(x) = {(8, 3), (4, 1), (0, –1), (–4, –3)}

g(x) = {(–4, –3), (0, –1), (4, 1), (8, 3)}

g(x) = {(–8, –3), (–4, 1), (0, 1), (4, 3)}

g(x) = {(8, –3), (4, –1), (0, 1), (–4, 3)}
g(x) = {(3, 8), (1, 4), (–1, 0), (–3, –4)}

Choose a true statement.

g(x) is not a function because f(x) is not a function.

g(x) is not a function because f(x) is not one-to-one.

g(x) is a function because f(x) is one-to-one.

g(x) is a function because f(x) is not one-to-one.